Can a meditation app help my sleep? A cross-sectional survey of Calm users. - Jennifer Huberty (Public Library of Science (PLoS), 2021)
Use of mindfulness mobile apps has become popular, however, there is little information about subscribers' perceptions of app content and its impact on sleep and mental health. The purpose of this study was to survey subscribers to Calm, a popular mindfulness meditation app, to explore perceived improvements in sleep and mental health, evaluate what components of the app were associated with improvements in sleep and mental health, and determine whether improvements differed based on sleep quality. Calm subscribers who had used a sleep-related component in the last 90 days completed a Web-based investigator-developed survey and the Pittsburgh Sleep Quality Index. The survey included questions about using Calm for sleep, sleep disturbances, mental health diagnoses (i.e., anxiety, depression, PTSD) and perceived impacts of the app. Participants reported on the extent to which they felt that using Calm had improved their sleep and mental health. Most participants reported sleep disturbance, and almost half reported a mental health diagnosis. The majority of participants reported that using Calm helped them fall asleep, stay asleep, and get restful sleep. All sleep components were associated with perceived improvements in sleep disturbance. Severity of sleep disturbance moderated relationships between using Calm components and reporting improved sleep. Among subscribers with mental health diagnoses, most reported that Calm helped improve symptoms. Perceived improvement in anxiety and depression was associated with using Calm's meditation components but not Sleep Stories or music/soundscapes. Severity of sleep disturbance did not moderate relationships between using Calm components and reporting mental health improvements. Given the accessibility of app-based meditation, research is needed to evaluate the efficacy of meditation apps to improve sleep disturbance. While some sleep content may be helpful for sleep, more research is needed to test what specific content affects mental health.